Seizure Action Plans Do Not Reduce Health Care Utilization in Pediatric Epilepsy Patients. (March 2016) - Roundy, Lindsi M.; Filloux, Francis M.; Kerr, Lynne; Rimer, Alyssa; Bonkowsky, Joshua L.
Management of pediatric epilepsy requires complex coordination of care. We hypothesized that an improved seizure management care plan would reduce health care utilization and improve outcomes. The authors conducted a cohort study with historical controls of 120 epilepsy patients before and after implementation of a "Seizure Action Plan." The authors evaluated for differences in health care utilization including emergency department visits, hospitalizations, clinic visits, telephone calls, and the percentage of emergency department visits that resulted in hospitalization in patients who did or did not have a Seizure Action Plan. The authors found that there was no decrease in these measures of health care utilization, and in fact the number of follow-up clinic visits was increased in the group with Seizure Action Plans (4.2 vs 3.3, P = .006). However, the study was underpowered to detect smaller differences. This study suggests that pediatric epilepsy quality improvement measures may require alternative approaches to reduce health care utilization and improve outcomes.